The Phenomenon of Pranking the Millennial Generation: Between Sad Dzariah and Fath Dzariah - Ahmad Muhtadi Anshor (Tribakti: Jurnal Pemikiran Keislaman, 2022)
This study aims to formulate a model of contemporary Islamic law approach based on sad dzariah and fath dzariah towards the millennial generation's phenomenon and culture of pranking. There are various new phenomena and cultures in the current millennial era which are identical with moral damage and socio-cultural harm to Indonesian society, as is the culture of pranking by the millennial generation. This is because the current millennial generation's pranking phenomenon has various impacts on people's lives. This condition then raises several questions: First, how is the impact of the phenomenon and culture of pranking by the millennial generation on the socio-cultural formation of Indonesian society? Second, how are the sad dzariah and fath dzariah approach model responding to the impact of the millennial generation's phenomenon and culture of pranking on the socio-cultural formation of Indonesian society? The research method used to answer these questions is to use the library method with databases on books, articles, and various data from the media and research related to the cultural impact of pranking in Indonesia. The data that has been collected is then compiled descriptively and analyzed using the content analysis method to conclude. This study found that: First, although it has a positive impact, it turns out that the negative impact is more dominant in the phenomenon and culture of pranking in Indonesia. Second, sad dzariah and fath dzariah have the urgency to avoid pranks and the culture of pranking as a means to avoid crime.